Arrangement of dermal chromatophore units in a polymorphic species, Ranitomeya imitator - De Araujo Miles, Mallory (East Carolina University, 2021)
In the 1980s, Rainer Schulte became the first to describe a species of poison frog living in the Amazon rainforest: Ranitomeya imitator. Schulte's classification of R. imitator as a single species sparked immediate controversy, since the species is composed of several dispersed populations, each exhibiting a unique color pattern (Caldwell 1990). The phenotypic differences apparent to even a casual observer of the R. imitator complex beg the question: how different are these frogs beneath their colorful skin? The present study attempts to quantify histological differences between the four color morphs of R. imitator and to demonstrate that the most closely related morphs have the most similar histology. Two types of chromatophores--melanophores and xanthophores--were measured in over 2,000 images of integumentary tissue taken under a brightfield microscope. One-way ANOVA tests were used to compare the abundance of chromatophores in skin tissue of different colors and from different morphs. Black tissue was found to exclusively contain melanophores, and melanophore abundance varied little between color morphs. Yellow and orange tissue contained a combination of xanthophores and melanophores. Xanthophores were most abundant in orange tissue from the banded morph, followed by the varadero morph, then the striped morph. Melanophore abundance followed the opposite trend. Green skin tissue (from the striped and spotted morphs) contained fewer xanthophores and more melanophores than orange tissue. Histological differences observed in this study correspond with the timing of mimetic divergence events proposed by Twomey et al. 2016, suggesting that differences have accumulated in the morphs since their divergence (Twomey 2016). Additionally, poison glands were measured to determine whether any color morph might have greater capacity for sequestering alkaloid toxins than another. Significant statistical differences in poison gland abundance existed between three of the four color morphs. The varadero morph exhibited the greatest abundance of poison glands, in contrast to findings from previous field studies in which the varadero morph exhibited relatively low alkaloid content. This discrepancy suggests that alkaloid defenses may be influenced more by dietary availability of alkaloids than poison gland storage capacity. Furthermore, the banded morph, which exhibits the brightest aposematic colors, and the spotted morph, which exhibits the least bright colors, showed no significant differences in poison gland abundance, suggesting that variation in aposematic signal intensity across color morphs may not be quantitatively honest. Together, the histological differences found in this study provide another piece of evidence to support the hypothesis that persistent color polymorphism may indicate an early stage of speciation in the mimic poison frog, Ranitomeya imitator.
Keywords: color polymorphism; chromatophore units; Dendrobatidae; Divergence (Biology); Mimicry (Biology); Numbers of species